2006
DOI: 10.1021/jp058226h
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Multidimensional Franck−Condon Simulations to Assess Model Chemistries:  A Case Study on Phenol

Abstract: Multidimensional Franck-Condon simulations of the dispersed fluorescence spectra of phenol generated with geometries obtained from the highly correlated post-Hartree-Fock methods CASSCF, MRCI, and SACCI are presented. While the simulations based on CASSCF and MRCI optimized geometries are very similar to each other and fail to reproduce the experimentally measured intensities faithfully, the simulations obtained from SACCI optimized geometries are very close to the experimental spectra. The code developed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 21 publications
(52 reference statements)
4
90
1
Order By: Relevance
“…Finally, Klimusheva et al 15 reported values for M 7 , M 23 , M 24 , M 25 and M 27 that are in moderately good agreement with our calculated values, but we did not see any contributions from these vibrations in the present work, nor have they been reported by others.…”
supporting
confidence: 88%
“…Finally, Klimusheva et al 15 reported values for M 7 , M 23 , M 24 , M 25 and M 27 that are in moderately good agreement with our calculated values, but we did not see any contributions from these vibrations in the present work, nor have they been reported by others.…”
supporting
confidence: 88%
“…ClBz-h5 (Aldrich, 99.8% purity) or ClBz-d5 (Aldrich, 99 atom% D) vapour, each with the naturally-occurring ratio of 35 Cl: 37 Cl, was seeded in ~5 bar of argon carrier gas and the gaseous mixture was passed through a General Valve pulsed nozzle (750 μm, 10 Hz, opening time of 150 μs) to create a free jet expansion, and hence almost all transitions are from the ground state zero-point vibrational level. The focused, frequency-doubled output of the dye laser passed through a vacuum chamber where it perpendicularly intersected the free jet expansion between two biased electrical grids located in the extraction region of a time-offlight spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…10,11,12 It is noted that the experiments of Murakami et al 10 are two-photon excitation, followed by ionization, while the experiments by Anderson et al 11 and Walter et al 12 are one-photon excitation followed by ionization. The Ortiz group 13 have also employed high-resolution, one-photon excitation REMPI spectroscopy in a supersonic beam, to obtain photoionization spectra of the origin band of the S1 state of the 35 ClBz-h5 and 37 ClBz-h5 molecules at a rotational temperature of 1 K; this allowed them to determine the shift of the origin band between the 35/37 Cl isotopologues. They report a shift of 0.14 ± 0.02 cm -1 , which is within the resolution of the present work, and hence we do not expect to be able to discern this; however, shifts of vibrational bands can be larger, and this will be commented on later.…”
Section: A Neutral Clbz-h5mentioning
confidence: 99%
See 2 more Smart Citations